Heart rate variability and central hemodynamic parameters in patients with post3infarctial cardiosclerosis and chronic heart failure - A. D. Ibatov; M. G. Poltavskaya; A. L. Syrkin (Российский кардиологический журнал)
Autonomic regulation in patients with post-infarctial cardiosclerosis (PICS) and chronic heart failure (CHF) was investigated. Eighty-eight patients with PICS were examined. Various cardiovascular tests, heart rate variability, and central hemodynamic parameters were assessed with integral rheography method at rest and during orthotest in Groups 1 and 2. Group 1 included patients with PICS and CHF, Group 2 - with PICS only. Compared with Group 2, Group 1 had more pronounced abnormalities of sympathic and parasympathic autonomic nervous system (ANS), lower heart rate variability, autonomic shift to sympathic hypertonus, and less balanced reaction to orthotest. Such a dynamics of heart rate variability and hemodynamic parameters at rest as well as during orthotest in patients with PICS and CHF is an evidence of more advanced disturbancies of autonomic regulation and hemodynamics in this clinical group.